Effects of three exercise interventions on inhibitory control in college students with internet addiction: a functional near-infrared spectroscopy study - Nie, Zhimin; Fan, Hainan (Frontiers in Psychology, 2025)
BackgroundInternet addiction (IA) poses a significant public health challenge, particularly among college students. Neurocognitive research points to dual inhibitory deficits as core mechanisms: impaired response inhibition drives impulsive loss of control, while deficient interference suppression heightens cue reactivity. While exercise shows potential for cognitive enhancement, its modality-specific effects on these distinct inhibitory subcomponents and underlying neurobiology remain unclear, hindering targeted interventions.MethodsThis study employed a multi-modal intervention design with IA-diagnosed college students. Participants underwent supervised 8-week programs across three exercise modalities: Footbike, swimming, and basketball. Inhibitory control was assessed pre- and post-intervention using standardized cognitive tasks (Go/No-Go for response inhibition, Flanker for interference suppression), with concurrent neurofunctional monitoring via functional near-infrared spectroscopy (fNIRS) focusing on prefrontal subregions—dorsolateral prefrontal cortex (DLPFC), frontopolar cortex (FPC), and orbitofrontal cortex (OFC).ResultsFootbike training demonstrated superior efficacy in enhancing inhibitory control compared to other modalities. It yielded significant improvements in both response inhibition (d = −1.67, 95% CI [−2.27, −1.07], p < 0.001) and interference inhibition (d = −0.78, 95% CI [−1.32, −0.25], p = 0.007), with neuroimaging revealing increased activation in associated regions including the DLPFC (d = 0.82, 95% CI [0.28, 1.35], p = 0.008) and FPC (d = 1.77, 95% CI [1.16, 2.38], p < 0.001). For interference inhibition function, basketball intervention showed significant improvement (d = −0.69, 95% CI [−1.22, −0.16], p = 0.005) and most strongly activated the OFC (d = −1.05, 95% CI [−1.06, −0.50], p = 0.004), though its effect on response inhibition was weaker. Swimming failed to demonstrate significant modality-specific benefits for any inhibitory domain. Distinct patterns of neural engagement across exercise types revealed dissociable neurocognitive pathways for inhibitory enhancement.ConclusionExercise modalities have distinct effects on IA-related inhibitory deficits: Footbike optimally enhances both subcomponents via DLPFC/FPC-mediated executive control, while basketball mainly engages OFC reward pathways with limited transfer. These findings provide a neurobiological basis for precision exercise prescriptions, identifying Footbike as optimal for dual inhibition deficits in IA. We propose a stratified framework using real-time fNIRS neurofeedback to match neurocognitive profiles with tailored exercise, advancing personalized interventions for addiction.